PENAMBAHAN REBUSAN DAUN SIRIH (Piper Bettle Linn) DAN REBUSAN DAUN JAMBU BIJI (Psidium Guajava) TERHADAP PRODUKSI KARKAS AYAM BROILER PERIODE STARTER - Alfryano A. Ade; Ni Putu S. Suryatni; Jonas F. Theedens (JURNAL NUKLEUS PETERNAKAN, 2021)
This study was conducted to examine the effect of adding boiled betel leaf and guava leaf in drinking water to the broiler chicken carcass production. As much 96 broilers strain CP 707 produced by PT Charoen Pokphan Indonesia. The experimental design used in this study was a completely randomized design (CRD) with 4 treatments and 6 replications. The treatments consisted of T0: Dringking water without boiled betel leaf and guava leaf, T1: Dringking water + boiled betel leaf as much as 50 mL per liter of dringking water, T2: Dringking water + boiled guava leaf as much as 50 mL per liter of dringking water, T3: Dringking water + boiled mixture of 25 mL boiled betel leaf + 25 mL boiled guava leaf per liter of dringking water. Result of the study showed that the treatment had no significant effect (P>0,05) on slaughtering weight, carcass percentage, non-carcass percentage and abdominal fat percentage of broiler chicken. Based on the result of this study, it can be concluded that the addition of boiled betel leaf 50 mL per liter of dringking water, guava leaf 50 mL per liter of dringking water and the addition of a mixture of 25 mL boiled betel leaf + 25 mL boiled guava leaf per liter of dringking water, gives the same effect on the parameters measured.